Development Of Paddy Seed Management By Using Long Range Passive Rfid Technology At Ultra High Frequency Band - Salleh, Azahari; Mohamad, Najmiah Radiah; Hashim, Nik Mohd Zarifie; Abd Aziz, Mohamad Zoinol Abidin; Zakaria, Zahriladha; Ab Hadi, Nik Azran (Research India Publications, 2015)
-